Afiliasi Mazhab Fiqh Tarekat SiddÃ®qÃ®yah di Jombang - Zuhdi, Zaenu (MarÃƒÂ¢ji`: Jurnal Ilmu Keislaman, 2014)
This article tried to look at the fiqh school affiliation of SiddÃ®qÃ®yah Tariqa in Jombang which has certain patterns of worship. Most of rituals conducted by adherents of this Tariqa shows that they conducted the rituals in ShÃ¢fiâÃ® school way. Yet in some cases there are few things which are quite different to the ShÃ¢fiâÃ® school. There are two possible causes. First, adherents of the Tariqa follow the opinion of their murshid. Second, they follow the opinion of the other three Sunni schools, Hanafi, MÃ¢likÃ®, and HanbalÃ®, though it is insignificant. Different ways of the ritual occur when the murshid issued fatwa on different opinion from the ShÃ¢fiâÃ® school. As long as the murshid does not issue a fatwa which is different with the ShÃ¢fiâÃ® school, the majority of the Tariqa adherents remain affiliate to the ShÃ¢fiâÃ® school. Furthermore, when the Tariqa adherents study fiqh more deeply and compare the fiqh schools, they follow the stongest argument of the schools eventough it is not ShÃ¢fiâÃ® school. However, this phenomenon is rarely happen for the adherents of the SiddÃ®qÃ®yah Tariqa in Jombang as their knowledge in fiqh is not deep enough. Their affiliated school of fiqh is mosty influenced by the social and cultural conditions surrounding them, as well as education and religious knowledge of the adherents.